Analytical solution for a cylindrical contact with reverse slip. (April 2013) - Vázquez, Jesús; Navarro, Carlos; Domínguez, Jaime
This article details the equations describing the contact between a cylindrical punch and a half plane when the punch is initially pressed against the medium with a constant normal force, N, followed by the simultaneous application of a tangential force, Q, and a bulk stress parallel to the surface, σ, with a ratio among loads such that it produces reverse slip at the edge of the contact. Both bodies were assumed to be elastic and made of the same material. Additionally, the contact semi-width, a, was assumed to be small relative to the radius, R, of the indenter, and as a result, the two bodies behaved as half planes. Elastic plane strain conditions have been considered. The equations describing surface stress are graphically illustrated for easy interpretation.